NOT QUITE HICKAM’S DICTUM - H, Joyce Soo Synn; W, Sau Wei; W, Loo Ling (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Myasthenia gravis is a rare autoimmune neuromuscular disease. Rarer still is the combination of myasthenia gravis and Graves’ disease, especially so in the paediatrics population, bringing to mind Hickam’s Dictum. However, considering that both diseases are antibody-mediated, it should not be surprising to find them occurring simultaneously. Of more concern, though, is the effect these diseases have on each other’s natural progression, and the challenges in managing them. Indeed, it has been observed that concurrent myasthenia gravis worsens hyperthyroidism, and improved thyroid function worsens muscle weakness. CASE We present a 3-year-old girl with concurrent exophthalmos and ptosis, diagnosed to have ocular myasthenia gravis and Graves’ disease. We discuss the course of her disease and challenges in managing it. The course of her disease was as reported in adults, where her hyperthyroidism was difficult to control, and her ophthalmoplegia worsened when her hyperthyroidism improved. CONCLUSION We are reminded that the presence of exophthalmos and ptosis simultaneously should ring warning bells of concurrent myasthenia gravis and Graves’ disease.